Analysis of T and NK cell subsets in the Sicilian population from young to supercentenarian: The role of age and gender. (17th June 2021) - Ligotti, Mattia Emanuela; Aiello, Anna; Accardi, Giulia; Aprile, Stefano; Bonura, Floriana; Bulati, Matteo; Gervasi, Francesco; Giammanco, Giovanni M.; Pojero, Fanny; Zareian, Nahid; Caruso, Calogero; Farzaneh, Farzin; et al.
Summary: Ageing dramatically affects number and function of both innate and adaptive arms of immune system, particularly T cell subsets, contributing to reduced vaccination efficacy, decreased resistance to infections and increased prevalence of cancer in older people. In the present paper, we analysed the age‐related changes in the absolute number of lymphocytes in 214 Sicilian subjects, and in the percentages of T and natural killer (NK) cells in a subcohort of donors. We compared these results with the immunophenotype of the oldest living Italian supercentenarian (aged 111 years). The results were also sorted by gender. The correlation between number/percentage of cells and age in all individuals. and separately in males and females, was examined using a simple linear regression analysis. We did not record the increase in the rate of inversion of the CD4/CD8 ratio, frequently reported as being associated with ageing in literature. Our observation was the direct consequence of a flat average trend of CD4 + and CD8 + T cell percentages in ageing donors, even when gender differences were included. Our results also suggest that CD4 + and CD8 + subsets are not affected equally by age comparing females with males, and we speculated that gender may affect the response to cytomegalovirus (CMV) infection. The supercentenarian showed a unique immunophenotypic signature regarding the relative percentages of her T cell subsets, with CD4 + and CD8 + T cell percentages and CD4 + naive T cell values in line with those recorded for the octogenarian subjects. This suggests that the supercentenarian has a naive 'younger' T cell profile comparable to that of a >80‐year‐old female. Abstract : We investigated age‐related changes in the absolute number of lymphocytes among 216 Sicilian subjects (age range 22‐111) and in the percentages of circulating lymphocyte subsets in a smaller group of donors of different ages. The data were also analyzed by gender. The supercentenarian has a naïve 'younger' T cell profile comparable to that of an older female.